A comparison of three- and two-rod constructs in the correction of severe pediatric scoliosis. (April 2023) - Machida, Masayoshi; Rocos, Brett; Zeller, Reinhard; Lebel, David E
Purpose: Managing severe scoliosis is challenging and risky with a significant complication rate regardless of treatment strategy. In this retrospective comparative study, we report our results using a three-rod compared to two-rod construct in the surgical treatment of severe spine deformities to investigate which technique is safer, and which provides superior radiological outcomes. Methods: Forty-six consecutive patients undergoing posterior spine fusion for scoliosis between 2006 and 2017 were identified in our institutional records. Inclusion criteria were minimum coronal deformity of 90°, age < 18 years at the time of surgery and a minimum 2 years of follow-up. Radiographic and clinical parameters, as well as post-operative complications were compared between the two groups. Results: There were 21 patients in the three-rod group and 25 in the two-rod group. The mean preoperative major coronal deformity was 100°± 9 and 102°± 10 in the three-rod and two-rod, respectively ( p  = 0.6). The average major curve correction was 51% and 59% in three-rod and two-rod groups, respectively ( p  = 0.03). The post-operative thoracic kyphosis was 30°± 11 and 21°± 12 in the three-rod and the two-rod groups, respectively ( p  = 0.01). The surgical time was 476 ± 52 and 387 ± 84 min in three-rod and two-rod, respectively ( p  < 0.01). One patient in the two-rod cohort showed permanent post-operative sensory deficit. There were three unplanned returns to operating theater in the two-rod group. Conclusions: Coronal correction was better with two-rod, whereas sagittal balance was superior with three-rod. Both techniques achieved balanced spine treating severe scoliosis. The two-rod technique was associated with a higher likelihood of requiring revision surgery. Level of evidence: level 3.